Pelatihan Teknis “Prompt Engineering” dalam Pemanfaatan AI Chat GPT untuk Meningkatkan Kemampuan Menulis Artikel Ilmiah Mahasiswa Baru - Annas, Annisa Nuraisyah; Lestari, Dwi Pratiwi; Lestari, Rini; Hanim, Siti Aisyah; Malay, Irvan (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This study aims to improve the scientific article writing competence of freshmen through AI-based prompt engineering technical training ChatGPT. The training is designed to address academic literacy challenges, especially in compiling article outlines, developing logical arguments, and effectively constructing technical language by utilizing artificial intelligence. The implementation method adopts the Student Creativity Program (PKM) scheme which involves three main stages: (1) an interactive workshop for introducing the principles of prompt engineering, (2) a simulation of using ChatGPT in drafting articles, and (3) collaborative mentoring to improve scientific structure and content. Participants consisted of 30 first-year multidisciplinary students who were evaluated through pretests and posttests to measure improvements in ability. The results showed that this training succeeded in improving participants' abilities in three key aspects: consistency of narrative flow (87%), accuracy of use of technical terminology (92%), and efficiency of article preparation time (on average 35% faster). Qualitative analysis revealed that the integration of ChatGPT with prompt engineering techniques enabled students to produce structured article outlines and data-based arguments. The practical implication of this research is the formation of an innovative training model that can be adapted to strengthen the digital literacy of new students, while emphasizing the role of AI as a tool to support academic productivity in the generative era.